ANALISIS PRIORITAS BELANJA DESA PADA DANA DESA KAYU BAWANG KABUPATEN BANJAR - Rakhmatullah Rakhmatullah; Ruddy Syafruddin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
The aims of this research are to(1) find out the village expenditure in the Kayu Bawang village fund in Banjar Regency, and (2) find out the priority of village spending on the right village fund in developing Kayu Bawang Village, Banjar Regency.The Respondents in this study were 6 respondents who were considered influential in determining village spending in Kayu Bawang Village which was used in data processing by using AHP(Analytical Hierarchy Process).The results of this study indicate that the alternative criteria for RPJMDes, Village Potential and Village Problems influence the determination of village expenditure priorities in the order of preference value of 54% RPJMDes, 30% Village Problems and 16% Village Potential. Based on these alternative criteria, the preference for village development priorities is 42%, community empowerment is 32%, community development is 20%, and village administration is 6%. With the most dominant conclusion, village development is 42%.Keywords:Priority, Village Expenditure, Village Government Organizers, Village   Development, Community Empowerment, Community Development, AHP ((Analytical Hierarchy Process) Method.